AB1289 TESTING DIFFERENT ITEMS INCLUDED IN THE DEFINITION OF REMISSION IN A MULTICENTRE SLE COHORT. (June 2019) - Saccon, Francesca; Zen, Margherita; Gatto, Mariele; Margiotta, Domenico Pe; Ceccarelli, Fulvia; Frontini, Giulia; Moroni, Gabriella; Bortoluzzi, Alessandra; Govoni, Marcello; Signorini, Viola; Mosca, Marta; Dall'ara, Francesca; et al.
Abstract : Background: Remission is the most desirable target in the treatment systemic lupus erythematosus (SLE) however, a universally accepted definition of remission in SLE is still missing. Objectives: To test the contribution of the different items included into the currently used definitions of remission in SLE. Methods: We studied 646 Caucasian patients from a multicentre lupus cohort followed for at least 5-years: female 585 (90.6%), mean age at baseline 40.59±12.14 years, mean disease duration 9.18±6.86 years. Disease activity was assessed by clinical SLE Disease Activity Index 2000 (cSLEDAI) and SELENA-SLEDAI physician global assessment (PGA), and damage by Systemic Lupus International Collaborating Clinics/ACR Damage Index (SDI). To test the performance of the different items included in the definitions of SLE remission [1, 2] we identify 7 subtypes of remission: (1) PGA (0-3)<0.5; (2) cSLEDAI=0; (3) prednisone (PDN)≤5mg/day; (4) PGA<0.5 and PDN≤5mg/day; (5) cSLEDAI=0 and PGA<0.5; (6) cSLEDAI=0 and PDN≤5mg/day; (7) cSLEDAI=0 and PDN≤5mg/day and PGA<0.5. The effect of remission on SDI was evaluated by Poisson regression analysis. Results: The number of patients achieving remission according to the different definitions is show in Figure 1 . The proportion of patients who maintained prolonged remission (5-consecutive years) was: PGA<0.5 13.0%; cSLEDAI=0 18.4%; PDN≤5mg/day 34.4%; PGA<0.5 and PDN≤5mg/day 12.5%; cSLEDAI=0 and PGA<0.5 12.7%; cSLEDAI=0 and PDN≤5mg/day 16.6%; cSLEDAI=0 and PDN≤5mg/day and PGA<0.5 12.4%. When PGA<0.5 was added to csledai, 198 (30.7%) patients lost 353 years in remission (1.8 years/patient): among them 195 (98.5%) showed a 0.5≤pga≤1 suggesting a low disease activity state (lda). when, pga<0.5 was added to csledai =0 and pdn ≤5mg/day, 151 (23.5%) patients lost 254 years in remission (1.7 years/patient): among them 149 (98.0%) showed a 0.5≤pga≤1 suggesting again lda. all remission subtypes were protective against damage (p<0.001), however csledai=0 showed the best performance (lower aic) (table 1 ). at multivariate analysis all remission subtypes lasting ≥2 consecutive years were protective against damage (p<0.001), except pdn≤5mg/day which was protective after 4 consecutive years. Conclusion: The prevalence and extent of damage significantly decreased as the time spent in remission increased, irrespective of the remission subtype. The addition of PGA<0.5 to cSLEDAI=0 or to cSLEDAI=0 and PDN≤5mg/day results in a decrease in the time spent in remission without significant difference in damage accrual. References: [1] van Vollenhoven R, et al. 2014 [2] Zen M, et al. 2015 Disclosure of Interests: Francesca Saccon: None declared, Margherita Zen: None declared, Mariele Gatto: None declared, Domenico PE Margiotta: None declared, Fulvia Ceccarelli: None declared, Giulia Frontini: None declared, Gabriella Moroni: None declared, Alessandra Bortoluzzi: None declared, Marcello Govoni: None declared, Viola Signorini: None declared, Marta Mosca Paid instructor for: GlaxoSmithKline, Lilly, UCB, Francesca Dall'Ara: None declared, Angela Tincani Consultant for: UCB, Pfizer, Abbvie, BMS, Sanofi, Roche, GSK, AlphaSigma, Lillly, Jannsen, Cellgene, Novartis, Anna Chiara Frigo: None declared, Antonella Afeltra Grant/research support from: MSD, PFIZER, ABBVIE, ROCHE, UCB, Speakers bureau: MSD, PFIZER, BMS, ROCHE, SANOFI, fabrizio conti: None declared, Andrea Doria: None declared